MtDNA sequence diversity of Hazara ethnic group from Pakistan. (September 2017) - Rakha, Allah; Fatima,; Peng, Min-Sheng; Adan, Atif; Bi, Rui; Yasmin, Memona; Yao, Yong-Gang
Highlights: We analyzed mtDNA control region sequences of 319 Hazara individuals from Pakistan. Hazara has lower haplotype diversity than Kashmiri and Pathan of Pakistan. The matrilineal mtDNA composition of Hazara resembles that of Central Asian. The Hazara mtDNA data are available through EMPOP accession number EMP00680. Abstract: The present study was undertaken to investigate mitochondrial DNA (mtDNA) control region sequences of Hazaras from Pakistan, so as to generate mtDNA reference database for forensic casework in Pakistan and to analyze phylogenetic relationship of this particular ethnic group with geographically proximal populations. Complete mtDNA control region (nt 16024-576) sequences were generated through Sanger Sequencing for 319 Hazara individuals from Quetta, Baluchistan. The population sample set showed a total of 189 distinct haplotypes, belonging mainly to West Eurasian (51.72%), East & Southeast Asian (29.78%) and South Asian (18.50%) haplogroups. Compared with other populations from Pakistan, the Hazara population had a relatively high haplotype diversity (0.9945) and a lower random match probability (0.0085). The dataset has been incorporated into EMPOP database under accession number EMP00680. The data herein comprises the largest, and likely most thoroughly examined, control region mtDNA dataset from Hazaras of Pakistan.